2017
DOI: 10.1038/srep43596
|View full text |Cite
|
Sign up to set email alerts
|

All Biomass and UV Protective Composite Composed of Compatibilized Lignin and Poly (Lactic-acid)

Abstract: Utilization of carbon-neutral biomass became increasingly important due to a desperate need for carbon reduction in the issue of global warming in light of replacing petroleum-based materials. We used lignin, which was an abundant, low cost, and non-food based biomass, for the development of all biomass-based films and composites through reactive compatibilization with poly (lactic-acid) (PLA). Using a facile and practical route, the hydrophilic hydroxyl groups of lignin were acetylated to impose the compatibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 41 publications
9
62
1
Order By: Relevance
“…PLA film showed a high transparency, since it exhibited a high transmittance percentage in the entire measured wavelength region. The addition of LNP reduced the transmittance in the visible region, reaching rather null values at wavelength lower than 350 nm in the UV region, demonstrating the potential applicability of PLA_LNP as all-biomass packaging and coating systems characterized by exceptional transparency and UV-protection capability, mainly significant for light-sensitive products (Kim et al, 2017). A food packaging material is expected to be transparent to visible light and opaque in the UV region, in order to protect the food from the oxidative deterioration, discoloration and flavors losses causes by the UV radiation (Li et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…PLA film showed a high transparency, since it exhibited a high transmittance percentage in the entire measured wavelength region. The addition of LNP reduced the transmittance in the visible region, reaching rather null values at wavelength lower than 350 nm in the UV region, demonstrating the potential applicability of PLA_LNP as all-biomass packaging and coating systems characterized by exceptional transparency and UV-protection capability, mainly significant for light-sensitive products (Kim et al, 2017). A food packaging material is expected to be transparent to visible light and opaque in the UV region, in order to protect the food from the oxidative deterioration, discoloration and flavors losses causes by the UV radiation (Li et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The UV blocking test results indicated high UV absorption with higher than 97.5% UV blocking. These results demonstrated the prospective of using lignin-containing films as attractive biomass-based packaging and coating material, having excellent transparency and UV protection capability, mostly essential for light-sensitive products The preparation of biomass-based films through reactive compatibilization of lignin with poly (lactic acid) (PLA) has also been examined [44]. Using a facile and practical route, the hydrophilic hydroxyl groups of lignin were acetylated to impose the required compatibility with PLA.…”
Section: Lignin As Uv Blocker For Packaging and Transparent Filmsmentioning
confidence: 98%
“…Regarding the effect of the nanoparticles, it can be observed that the nanocomposites show higher WVTR values than both unfilled PLAV and PLAR samples, which could be explained by the hydrophilic nature of the YMNs due to the high amount of -OH groups. In this context, Kim et al [59] studied the WVTR of PLA reinforced with pristine lignin and acetylated lignin, reporting higher WVTR values for the PLA-lignin composites in comparison with neat PLA. This behavior was ascribed to the hydrophilic nature of pristine lignin.…”
Section: Barrier Propertiesmentioning
confidence: 99%